2005
DOI: 10.1007/s00701-005-0650-z
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of 77 patients harbouring lumbar synovial cysts: Functional and neurological outcome

Abstract: Surgical resection of lumbar synovial cysts is an effective treatment associated with very low morbidity. Synovial cysts are associated with increased grade and frequency of facet joint asteoarthritis but not with increased grade or frequency of degenerative disc disease compared with patients without cysts. In the author's opinion, at the present time, there is no reliable criterion which allows the development of a symptomatic spinal instability to be predicted in patients with a preoperative spondylolisthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 18 publications
4
85
0
10
Order By: Relevance
“…The fact that repetitive minor injuries may go unnoticed and not come up in the patient's medical history, along with the fact that these injuries usually happen more at the mobile parts of the spine, suggests that the pathogenetic roles of instability and trauma are intertwined. The definite association with osteoarthritis (40.5%) and spondylolisthesis (43.4%) and the reported relationship with disc degeneration (13.2%) only highlight the major role of segmental spinal instability in the pathogenesis of spinal synovial cysts [10,21,26,31,34,35,44,47] (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that repetitive minor injuries may go unnoticed and not come up in the patient's medical history, along with the fact that these injuries usually happen more at the mobile parts of the spine, suggests that the pathogenetic roles of instability and trauma are intertwined. The definite association with osteoarthritis (40.5%) and spondylolisthesis (43.4%) and the reported relationship with disc degeneration (13.2%) only highlight the major role of segmental spinal instability in the pathogenesis of spinal synovial cysts [10,21,26,31,34,35,44,47] (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…In that context, spinal instability and spinal trauma play a major role [16]. Trauma, although not so strongly incriminated by some authors [21,26,31,35] undoubtedly exercises a cumulative effect in spinal degeneration. Yarde et al [47] reported the presence of hemosidirin in six out of eight patients with LISCs, of whom only one had a clear history of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…21) These lesions usually present with common symptoms of radiculopathy, neurogenic claudication, myelopathy, neurological deficit, and even cauda equina syndrome. 18,23) Here we discuss our experience with various types of lumbar spinal synovial cyst, including the evaluation, treatment modalities, and pathologies in the differential diagnosis of lumbar radiculopathy, especially in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cystic lesion embedded in the inner surface of the LF with no epithelial lining or continuity with the facet joint synovium is classified as LF cyst 1,3) , and cystic lesion located in the PLL with the same properties is classified as PLL cyst 11) . These lesions usually present with common symptoms of radiculopathy, neurologic claudication, myelopathy, neurological deficit, and even cauda equina syndrome 10,12) .…”
Section: Discussionmentioning
confidence: 99%